Cerebral Organoid Research Ethics and Pinning the Tail on the Donkey - McKeown, Alex (Cambridge quarterly of healthcare ethics, 2023)
The risk of creating cerebral organoids/assembloids conscious enough to suffer is a recurrent concern in organoid research ethics. On one hand, we should, apparently, avoid discovering how to distinguish between organoids that it would be permissible (non-conscious) and impermissible (conscious) to use in research, since if successful we would create organoids that suffer. On the other, if we do not, the risk persists that research might inadvertently continue to cause organoids to suffer. Moreover, since modeling some brain disorders may require inducing stress in organoids, it is unclear how to eliminate the risk, if we want to develop effective therapies. We are committed to harm avoidance but hamstrung by a presumption that we should avoid research that might tell us clearly when suffering occurs. How can we negotiate this challenge and maximize the therapeutic benefits of cerebral organoid research? The author interrogates the challenge, suggesting a tentative way forward.